The Influence of Village Apparatus Competence, Whistleblowing and Internal Control System on Prevention Fraud in Village Financial Management - Restu Abdul Baki; Ismet Ismatullah (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
This study aims to determine the effect of village apparatus competence, Whistleblowing and internal control systems on prevention Fraudin village financial management carried out in Ciwaru village, Mekarsakti village and Mandrajaya village, Ciemas district, Sukabumi district, this study uses quantitative research methods with a quantitative approach. parametric statistics for data collection techniques using questionnaires, interviews, literature and documentation, the number of samples In this study as many as 100 people, when the questionnaire was distributed, the researcher would spread the number of questionnaires more than the predetermined number of samples, namely as much as the number of samples added 10% of the sample namely 100 people plus 10% or as many as 110 questionnaires which will be distributed to 110 people. The data analysis technique used is validity test, reliability test, classical assumption test, multiple regression test, and hypothesis testing. This research was assisted by SPSS24 software by coming to the conclusion that the competence of village apparatus has no significant effect on the prevention of Fraud in village financial management, while Whistleblowing and internal control systems are positively and significantly impacted on the prevention of Fraud in village financial management in Ciwaru Village, MekarsaktiVillage and Mandrajaya Village, CiemasSubdistrict, Sukabumi Regency.